2022
DOI: 10.1098/rstb.2020.0441
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene regulatory signatures of dominance rank and social bond strength in wild baboons

Abstract: The social environment is a major determinant of morbidity, mortality and Darwinian fitness in social animals. Recent studies have begun to uncover the molecular processes associated with these relationships, but the degree to which they vary across different dimensions of the social environment remains unclear. Here, we draw on a long-term field study of wild baboons to compare the signatures of affiliative and competitive aspects of the social environment in white blood cell gene regulation, under both immun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 126 publications
4
35
4
Order By: Relevance
“…We found no support for the second hypothesized mechanism that we explored to link sociality to survival; none of the measures of sociality analyzed influenced an individual's survival trajectory following injury. Despite a vast body of literature supporting differences in health and immunity between individuals of different social status [44,35,39], we found no evidence for an effect of social status on the survival trajectories of injured animals. These findings contrast with a previous study on wild baboons where high status males had faster healing rates than lower status males [37].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We found no support for the second hypothesized mechanism that we explored to link sociality to survival; none of the measures of sociality analyzed influenced an individual's survival trajectory following injury. Despite a vast body of literature supporting differences in health and immunity between individuals of different social status [44,35,39], we found no evidence for an effect of social status on the survival trajectories of injured animals. These findings contrast with a previous study on wild baboons where high status males had faster healing rates than lower status males [37].…”
Section: Discussioncontrasting
confidence: 95%
“…Growing literature has supported a strong relationship between the social environment and survival in many mammal species [3], but the ultimate function of some components of sociality, such as social relationships, remain unclear [77]. Although sociality has been demonstrated to enhance health and immunity [44,35,45], here we showed that these benefits did not translate to an improved ability to cope with the risk of death from injuries. Instead, we found that sociality plays an important role in preventing individuals from suffering injuries that would likely lead to death.…”
Section: Discussioncontrasting
confidence: 56%
“…A few cross-cutting themes emerge from the contributions to this theme issue as vibrant areas of ongoing or future progress, supporting the suggestion by Hobson [5] that we may be entering a more cross-disciplinary phase in the study of dominance hierarchies. Many contributions highlight the rapid development of advanced quantitative tools for social network analysis as playing an important role in driving new insight into the structure and function of dominance hierarchies (Tibbetts et al [67] and Dehnen et al [75]), comparative approaches (Strauss et al [22]), theoretical frameworks (Lewis [69], Zeng et al [24] and Strauss & Shizuka [78]) and modelling (Hamilton & Benincasa [76]), the theme issue highlights how research into dominance hierarchies uses the full breadth of tools available to modern biologists.…”
Section: Discussionmentioning
confidence: 99%
“…[ 74 ]), long-term individual-based observational studies (Anderson et al . [ 67 ] and Dehnen et al . [ 75 ]), comparative approaches (Strauss et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation